Assessment of liver fibrosis using pharmacokinetic parameters of dynamic contrast‐enhanced magnetic resonance imaging. Issue 1 (28th December 2015) - Li, Zhiming; Sun, Jihong; Chen, Lumin; Huang, Ning; Hu, Peng; Hu, Xi; Han, Guocan; Zhou, Yurong; Bai, Weixian; Niu, Tianye; Yang, Xiaoming
Abstract : Purpose: To evaluate the pharmacokinetic parameters of dynamic contrast‐enhanced magnetic resonance imaging (DCE‐MRI) in diagnosing and staging liver fibrosis in rabbits. Materials and Methods: DCE‐MRI with gadodiamide (Gd‐DTPA‐BMA) was performed on a 3.0 Tesla, 60 cm bore MR scanner for rabbits with CCl4 ‐induced liver fibrosis, and an untreated control group. Fibrosis was staged according to the METAVIR system: control (F0; n = 13), nonadvanced fibrosis (F1–2; n = 15), and advanced fibrosis (F3–4; n = 12). The DCE‐MRI parameters K trans, kep, Ve, and vp were measured with a dual‐input extended Tofts model. Receiver operating characteristic analyses were performed to assess the diagnostic performance of K trans, Ve, and vp in staging liver fibrosis. Results: Both K trans and Ve decreased with increasing fibrosis stage. K trans of the control group was significantly different from that of the overall fibrosis group, nonadvanced group, and advanced group ( P < 0.001 for all). Significant differences were found between Ve of the control group and that of the overall fibrosis and advanced groups ( P = 0.019 and P = 0.009, respectively). For K trans, the areas under the receiver operating characteristic curve (AUROCs) for discriminating the control group from the overall fibrosis and advanced fibrosis groups were 0.909 (95% confidence interval [CI], 0.809–1.000), and 0.936 (95% CI, 0.847–1.000), respectively. For discriminating between the control and nonadvanced fibrosis groups, the AUROC of K trans was 0.887 (95% CI, 0.762–1.000). The AUROCs of K trans were higher than those of Ve and vp for discriminating between the control and overall fibrosis groups, the control and nonadvanced fibrosis groups, and the control and advanced fibrosis groups. Pharmacokinetic parameters were negatively correlated with fibrosis stage (K trans, rho = ‐0.668, P < 0.001; Ve, rho = ‐0.438, P = 0.005; vp, rho = ‐0.360, P = 0.023). Conclusion: Among pharmacokinetic parameters of DCE‐MRI in our study, K trans was an excellent predictor for differentiating fibrotic livers from normal livers, and differentiating normal livers from nonadvanced or advanced fibrosis livers. J. Magn. Reson. Imaging 2016;44:98–104.